La transformation du mouvement républicain irlandais des années 1980 à la problématique posée par le Brexit - Yann Bévant (Revue Française de Civilisation Britannique)
The Northern Irish question is the product of conflicting community interests, and as a consequence of diverging constructions of History. Contemporary Irish republicanism is one of those constructions. It was characterised by its numerous splits connected to the “messianic” spirit of its non-negotiable doctrine. The growing participation of the movement to political processes and the acceptance of the Good Friday Agreement presided over a new pragmatic approach based on tolerance and inclusiveness epitomised by the association Coiste na nIarchimi. Sinn Fein and the republican movement have paradoxically become agents of political stability in Northern Ireland. Brexit, with the influence it exerts on loyalists, puts to the test this process started at the end of the previous century, as it brings the Border issue back to the centre of the Irish national question.